2010
DOI: 10.4085/1062-6050-45.6.601
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying After Pickle-Juice Ingestion in Rested, Euhydrated Humans

Abstract: Context: Small volumes of pickle juice (PJ) relieve muscle cramps within 85 seconds of ingestion without significantly affecting plasma variables. This effect may be neurologic rather than metabolic. Understanding PJ's gastric emptying would help to strengthen this theory.Objective: To compare gastric emptying and plasma variables after PJ and deionized water (DIW) ingestion.Design: Crossover study. Setting: Laboratory.Patients or Other Participants: Ten men (age 5 25.4 6 0.7 years, height 5 177.1 6 1.6 cm, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Whereas percentage changes in plasma volume can decrease 3% to 5% after PJ ingestion, 15,31 plasma volume changes were less than 1% over 60 minutes postingestion in my study. The discrepancy likely reflects the fact that earlier investigators provided larger volumes of PJ 31 to euhydrated 15 rather than hypohydrated individuals. Given that minor percentage changes in plasma volume occurred, one may assume thirst would be unaffected.…”
Section: Resultscontrasting
confidence: 69%
“…Whereas percentage changes in plasma volume can decrease 3% to 5% after PJ ingestion, 15,31 plasma volume changes were less than 1% over 60 minutes postingestion in my study. The discrepancy likely reflects the fact that earlier investigators provided larger volumes of PJ 31 to euhydrated 15 rather than hypohydrated individuals. Given that minor percentage changes in plasma volume occurred, one may assume thirst would be unaffected.…”
Section: Resultscontrasting
confidence: 69%
“…32 In our study, the gastric-emptying rates were likely low for all conditions due to the small volumes ingested and vigorous exercise. Miller et al 21 observed a gastric-emptying rate of approximately 2 mL per minute when rested, euhydrated participants ingested 1 bolus of PJ that was approximately 150 mL. In our study, plasma Na þ content increased only in the 2-bolus condition from 30 to 65 minutes.…”
mentioning
confidence: 38%
“…Second, participants did not exercise postingestion of PJ. [17][18][19]21 No researchers have examined the extracellular fluid space after individuals ingested PJ and then resumed exercise. Given that aldosterone increases during exercise, consuming a salty drink and resuming exercise may increase [Na þ ] p or OSM p because aldosterone increases Na þ absorption in the kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms have been observed after ingestion of salt tablets and large volumes of water, 29,30 large volumes of isotonic and hypertonic sodium drinks, 31 or large volumes of PJ (ie, 7 mL/kg body mass). 32 None of our participants experienced upset stomach or abdominal cramping after PJ ingestion, and finishing times were similar between trials.…”
Section: Plasma Volume and Time To Exhaustionmentioning
confidence: 98%